Development of Gas Sensor Array based on Phthalocyanines Functionalized TiO2/ZnO Heterojunction Thin Films - Jareena Begam Jakir Hussain; Sarathbavan Murugan; Gabriele Magna; Venkatramaiah Nutalapati; Surya Velappa Jayaraman; Corrado Di Natale; Yuvaraj Sivalingam (Proceedings, 2018)
Gas sensing properties of diverse phthalocyanines functionalized TiO2/ZnO heterojunction thin films were investigated respect to a number of volatile organic compounds (VOCs) in both dark and light conditions. These studies showed that influence of heterojunction along with functionalization alter the optical properties and gas sensing of sensors. Results show that each sensor exhibits a different pattern of relative sensitivity, and this feature can be used to discriminate among a wide range of VOCs.